2006
DOI: 10.2152/jmi.53.264
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical and immunohistochemical investigation of guanase and nedasin in human tissues

Abstract: : Guanase is known as an enzyme released from the liver. Recently, cloning and sequencing of the guanase gene were reported. In addition, almost simultaneously, it was reported that an unknown protein that binds to neuronal and endocrine lethal(1)-discs large (NE-dlg), one of the membrane-associated guanylate kinase homologues (MAGUK) family proteins involved in synaptic connection between neurons, was cloned and named nedasin (NE-dlg associated protein), whose sequence was almost identical to that of guanase.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Quantitative PCR analysis of heterogeneous tumor tissues cannot distinguish between expression levels in specific cellular phenotypes which might limit the discriminatory power of this method. Nevertheless, our observation of BAAT40 and GAD41, two enzymes involved in bile acid and purine metabolism in the adult liver, being weaker expressed in immature embryonal HB as compared to predominantly fetal tumors may suggest that high miR‐492 expression might be associated with the immature and advanced C2 type of HB. Interestingly, we detected a correlation of miR‐492 and KRT19 with the lack of β‐catenin mutation, a clinicopathological characteristic which was not associated with a distinct subgroup by the Cairo et al study 18.…”
Section: Discussionmentioning
confidence: 85%
“…Quantitative PCR analysis of heterogeneous tumor tissues cannot distinguish between expression levels in specific cellular phenotypes which might limit the discriminatory power of this method. Nevertheless, our observation of BAAT40 and GAD41, two enzymes involved in bile acid and purine metabolism in the adult liver, being weaker expressed in immature embryonal HB as compared to predominantly fetal tumors may suggest that high miR‐492 expression might be associated with the immature and advanced C2 type of HB. Interestingly, we detected a correlation of miR‐492 and KRT19 with the lack of β‐catenin mutation, a clinicopathological characteristic which was not associated with a distinct subgroup by the Cairo et al study 18.…”
Section: Discussionmentioning
confidence: 85%
“…The enzyme is highly expressed in liver, brain, kidney and placenta [26], [27]. Furthermore, GDA is also involved in the regulation of dendrite development as a positive regulator by modulating guanine concentrations [26].…”
Section: Resultsmentioning
confidence: 99%
“…GDA is a functional candidate based on its function as a regulator of dendrite patterning and synaptic formation between hippocampal neurons 25,26 and its involvement in dopamine and glutamate signaling. [27][28][29] Tannu et al 29 showed significant decrease in GDA in Rhesus monkeys following cocaine self-administration.…”
Section: Discussionmentioning
confidence: 99%